Inclusive education in initial teacher education in South Africa: practical or professional knowledge? - Walton, Elizabeth (South African Education Research Association, 2017)
Inclusive education is embedded in South African policy with the expectation that teacher education will equip pre-service teachers to teach inclusively. As a result, courses in inclusive education are offered in most Initial Teacher Education (ITE) programmes and research interest in teacher education for inclusion has grown. This paper contributes to this body of knowledge by using Legitimation Code Theory to engage critically with concepts and assessment tasks from three inclusive education courses. This meant identifying where theoretical, context independent knowledge is privileged (semantic density), and where the knowledge is derived from practice or experience and designed to be implemented within specific contexts (semantic gravity). Using examples as reference points, I discuss how inclusive education comes to emphasise practical knowledge, to be enacted in particular contexts, or with particular groups of learners. An alternative is to position inclusive education as professional knowledge where theoretically informed judgments are made in response to the complexity of learner diversity. This will require strengthening the disciplinary foundation of concepts presented in ITE courses in inclusive education.